A Look at the Mission of Wise Men - Pavas, Fabio Andres; Arzola de la Peña, Nelson (Ingeniería e Investigación, 2019)
This editorial note presents a brief review of the report by the 2019 Mission of Wise men. The note gathers the more general aspects and poses a discussion about the role that the Schools of Engineering can play in the framework of reference raised by the Mission.